RELATIONSHIP REGULATION OF F ARDHU PRAYER WITH STRESS LEVEL OF SEMESTER 8 STUDENTS FACULTY OF MEDICINE MUHAMMADIYAH UNIVERSITY PURWOKERTO - Rifaqul Azizi; Titik Kusumawinakhyu; Irma Finurina (International Islamic Medicine Forum, 2020)
Fardhu prayer is a compulsory activity that can create peace of mind for those who run it. For medical students in semester 8 of FK UMP who are experiencing many exams and personal problems, prayer can help calm and relieve stress. This study aims to determine the relationship between the regularity of fardhu prayer and stress levels in 8th-semester students of the Faculty of Medicine, Muhammadiyah University of Purwokerto. Methods use a correlational analysis research design with a cross-sectional approach. The study was conducted on an entire population of 48 students of the Faculty of Medicine, Muhammadiyah University of Purwokerto. Stress level data were obtained using the DASS test questionnaire, and prayer regularity data were obtained from the fardhu prayer regularity questionnaire. Data analysis with Pearson parametric correlation test. Results show the highest level of stress in students who experienced mild stress, and the results of the regularity of student prayers were found that many students regularly prayed. Based on the Pearson correlation test results, the value of p = 0.0 10 was obtained. There is a significant relationship between the regularity of fardhu prayer and the stress of the 8th-semester students of the Faculty of Medicine, Muhammadiyah University of Purwokerto, class of 2013.